Sodium vanadium phosphate composite positive electrode active material, preparation method thereof and sodium ion battery

By introducing a carbon cladding layer into the positive electrode active material of vanadium phosphate and optimizing the process, the problem of low electronic conductivity and compaction density of vanadium phosphate material is solved, and the energy density and cycling performance of sodium ion batteries are significantly improved.

CN119400834APending Publication Date: 2025-02-07三一红象电池有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411559476.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing low electronic conductivity of vanadium phosphate and low powder compaction density lead to insufficient energy density in practical applications.

Method used

A composite positive electrode active material of sodium vanadium phosphate is used, which includes a core of sodium vanadium phosphate and a carbon coating covering part of its surface. By optimizing the feeding sequence and process parameters, the compaction density of the material is improved.

Benefits of technology

The electronic conductivity and powder compaction density of the vanadium phosphate composite material have been significantly improved, and the energy density and cycling performance of sodium ion batteries have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400834A_ABST
    Figure CN119400834A_ABST
Patent Text Reader

Abstract

The invention relates to the field of sodium ion batteries, and discloses a sodium vanadium phosphate composite positive electrode active material, a preparation method thereof and a sodium ion battery. The sodium vanadium phosphate composite positive electrode active material comprises a sodium vanadium phosphate inner core and a carbon coating layer coating at least part of the surface of the sodium vanadium phosphate inner core; and the compaction density of the sodium vanadium phosphate composite positive active material is greater than 1.8 g / cm < 3 >. When the positive electrode active material with relatively high compaction density is applied to the sodium ion battery, the diffusion path of sodium ions can be reduced, the energy density of the battery is improved, the discharge capacity of the battery is increased, the internal resistance of the battery is reduced, the polarization loss is reduced, the voltage platform of the battery is improved, and the rate capability and the cycle performance of the battery are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of sodium ion batteries, and specifically to a sodium vanadium phosphate composite positive electrode active material and a preparation method thereof and a sodium ion battery. Background Art

[0002] Compared with lithium-ion batteries, sodium-ion batteries have a disadvantage in energy density due to the larger radius of sodium ions. However, the obvious advantage of abundant sodium resources makes sodium-ion batteries have great application prospects in large-scale energy storage, low-speed electric vehicles, 5G base stations, power tools, etc.

[0003] At present, the focus of sodium ion battery development is the development of positive electrode active materials. There are many types of positive electrode active materials for sodium ion batteries. According to the different crystal structures of the materials, the current popular positive electrode active materials for sodium ion batteries include layered transition metal oxides, polyanion compounds and Prussian blue compounds. Among them, polyanion compounds have a stable three-dimensional sodium ion channel structure, which can stably and quickly transport sodium ions, giving the battery cell a long cycle and high rate performance advantage, and thus showing great commercial potential. Among the polyanion compound materials, sodium vanadium phosphate (Na 3 V 2 (PO 4 ) 3 ) Due to its advantages such as high theoretical capacity, good rate performance and easy access to raw materials, it has gradually become the fastest active material for mass production of sodium ion battery cathodes. However, the low inherent electronic conductivity and low compaction density of sodium vanadium phosphate lead to its insufficient energy density in practical applications. Summary of the invention

[0004] In view of this, the present application provides a sodium vanadium phosphate composite positive electrode active material to solve the problems of low electronic conductivity and low powder compaction density of the existing sodium vanadium phosphate.

[0005] The present application also provides a method for preparing the above-mentioned sodium vanadium phosphate composite positive electrode active material to solve the problems of low electronic conductivity and low powder compaction density of sodium vanadium phosphate prepared by existing methods.

[0006] According to an embodiment of the present application, in the first aspect, the present application provides a sodium vanadium phosphate composite positive electrode active material, comprising a sodium vanadium phosphate core and a carbon coating layer coating at least a portion of the surface of the sodium vanadium phosphate core; the compaction density of the sodium vanadium phosphate composite positive electrode active material is greater than 1.8 g / cm 3 .

[0007] In an optional embodiment, the compaction density of the sodium vanadium phosphate composite positive electrode active material is 1.82 g / cm 3 -2.45g / cm 3 .

[0008] In an optional embodiment, based on the mass of the sodium vanadium phosphate composite positive electrode active material, the content of the carbon coating layer is 1%-6%.

[0009] In an optional embodiment, the chemical formula of the sodium vanadium phosphate core is Na 3+y V 2-x M x (PO 4 ) 3 , wherein M is at least one of Mn, Ti, Fe, and Al elements, 0≤x≤1, 0≤y≤0.5.

[0010] In an optional embodiment, the sodium vanadium phosphate composite positive electrode active material is a spherical particle with a particle size Dv50 of 6 μm-10 μm.

[0011] According to an embodiment of the present application, in a second aspect, the present application provides a method for preparing a sodium vanadium phosphate composite positive electrode active material, comprising the following steps:

[0012] S1. preparing raw materials: a vanadium source, a phosphorus source, a sodium source and a carbon source; mixing the vanadium source with a dispersant, or mixing the vanadium source with a dispersant and any one or two of a phosphorus source, a sodium source and a carbon source to form a first mixture, heating the first mixture to a first temperature and stirring for a first time;

[0013] Then, the remaining raw materials are added, and stirred at the first temperature for a second time to obtain a second mixture with a solid content of 30%-60%; the ratio of the first temperature to the boiling point of the dispersant is 0.6-0.9;

[0014] S2, sand-milling the second mixture obtained in S1 to obtain a third mixture;

[0015] S3, spray drying the third mixture obtained in S2 to obtain spherical particles;

[0016] S4. Heat-treating the spherical particles obtained in S3 in a protective atmosphere to obtain.

[0017] In an optional embodiment, the first time is 30 min-90 min.

[0018] In an optional embodiment, the second time is 30 min-60 min.

[0019] In an optional embodiment, the molar ratio of the sodium element in the sodium source to the vanadium element in the vanadium source and the phosphorus element in the phosphorus source is (3-3.1):2:3.

[0020] In an optional embodiment, the ratio of the mass of the carbon source to the total mass of the vanadium source, the phosphorus source and the sodium source is (0.02-0.2):1.

[0021] In an optional embodiment, the dispersant includes at least one of deionized water, anhydrous ethanol, anhydrous ether, and anhydrous methanol.

[0022] In an optional embodiment, the vanadium source includes at least one of vanadium trioxide, vanadium dioxide, vanadium pentoxide, vanadium acetylacetonate, vanadium dichloride, vanadium trichloride, vanadium sulfate, vanadium oxalate, vanadium acetylacetonate, sodium vanadate, sodium metavanadate, and ammonium metavanadate.

[0023] In an optional embodiment, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate.

[0024] In an optional embodiment, the sodium source includes at least one of trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium oxide, and sodium peroxide.

[0025] In an optional embodiment, the carbon source includes at least one of activated carbon, Ketjen black, carbon nanotubes, graphene, sucrose, cellulose, polyvinyl pyrrolidone, oleic acid, dopamine hydrochloride, oxalic acid, glucose, ascorbic acid, and citric acid.

[0026] In an optional embodiment, the particle size Dv50 of the third mixture is 0.3 μm-1 μm.

[0027] In an optional embodiment, the process parameters of the spray drying step include: pressure of 0.3MPa-0.6MPa, air inlet temperature of 210°C-260°C, and air outlet temperature of 100°C-130°C.

[0028] In an optional embodiment, the heating rate of the heat treatment step is 1°C / min-5°C / min, the calcination temperature is 600°C-850°C, and the calcination time is 6h-20h.

[0029] In an optional embodiment, S1 further includes the step of adding an M source to the first mixture before forming the first mixture or after heating;

[0030] The M source includes at least one of a Mn source, a Ti source, a Fe source, and an Al source, and / or the ratio of the sum of the molar numbers of the M element in the M source and the vanadium element in the vanadium source to the molar number of the phosphorus element in the phosphorus source is 2:3.

[0031] According to an embodiment of the present application, in a third aspect, the present application further provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode collector, wherein the positive electrode active material layer comprises the sodium vanadium phosphate composite positive electrode active material described in the first aspect of the present application or the sodium vanadium phosphate composite positive electrode active material prepared by the preparation method described in the second aspect of the present application.

[0032] According to an embodiment of the present application, in a fourth aspect, the present application further provides a sodium ion battery, comprising the positive electrode sheet described in the third aspect of the present application.

[0033] The technical solution of this application has the following advantages:

[0034] The sodium vanadium phosphate composite positive electrode active material provided in the present application comprises a sodium vanadium phosphate core and a carbon coating layer covering at least a portion of the surface of the sodium vanadium phosphate core; the compaction density of the sodium vanadium phosphate composite positive electrode active material is greater than 1.8 g / cm 3 When positive electrode active materials with higher compaction density are applied to sodium ion batteries, the diffusion path of sodium ions can be reduced, the energy density of the battery can be improved, the discharge capacity of the battery can be increased, the internal resistance of the battery can be reduced, the polarization loss can be reduced, the voltage platform of the battery can be increased, and the rate performance and cycle performance of the battery can be guaranteed.

[0035] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0037] Figure 1 This is an XRD comparison chart of the sodium vanadium phosphate composite positive electrode active material prepared in Example 1 and a sodium vanadium phosphate standard card.

[0038] Figure 2 This is a SEM image of the sodium vanadium phosphate composite positive electrode active material prepared in Example 1.

[0039] Figure 3 This is a cross-sectional SEM image of the sodium vanadium phosphate composite positive electrode active material prepared in Example 1.

[0040] Figure 4 This is a cycle curve diagram of the sodium vanadium phosphate composite positive electrode active material prepared in Example 1 after being assembled and charged.

[0041] Figure 5 This is a cross-sectional SEM image of the sodium vanadium phosphate composite positive electrode active material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0044] In order to solve the problems of low electronic conductivity and low powder compaction density of the existing sodium vanadium phosphate, according to the first aspect of the present application, a sodium vanadium phosphate composite positive electrode active material is provided, comprising a sodium vanadium phosphate core and a carbon coating layer covering at least a portion of the surface of the sodium vanadium phosphate core; the compaction density of the sodium vanadium phosphate composite positive electrode active material is greater than 1.8 g / cm 3 As an example, the compaction density of the sodium vanadium phosphate composite positive electrode active material in this application can be, for example, 1.82 g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 Equal or within the range formed by any two of the above values. Therefore, when the positive electrode active material with a higher compaction density is applied to a sodium ion battery, the diffusion path of sodium ions can be reduced, the energy density of the battery can be improved, the discharge capacity of the battery can be increased, the internal resistance of the battery can be reduced, the polarization loss can be reduced, the voltage platform of the battery can be increased, and the rate performance and cycle performance of the battery can be guaranteed.

[0045] Studies have shown that the carbon layer coating technology can improve the electronic conductivity of sodium vanadium phosphate. Therefore, the sodium vanadium phosphate composite positive electrode active material of the present application includes a carbon coating layer that coats at least part of the surface of the sodium vanadium phosphate core. The content of the carbon coating layer is 1%-6% based on the mass of the sodium vanadium phosphate composite positive electrode active material. In this way, the electronic conductivity of sodium vanadium phosphate can be effectively improved without affecting the charge and discharge capacity of sodium vanadium phosphate.

[0046] In an optional embodiment, the chemical formula of the sodium vanadium phosphate core is Na 3+y V 2-x M x (PO 4 ) 3 , wherein M is at least one of Mn, Ti, Fe, and Al, 0≤x≤1, 0≤y≤0.5. By doping Mn, Ti, Fe, Al and other elements at the V position of the sodium vanadium phosphate crystal structure, the intrinsic electronic conductivity of sodium vanadium phosphate can be improved, and the amount of carbon in the coating layer can be reduced, which helps to improve the compaction density of the material; and the use of doped elements to partially replace the more expensive vanadium can also greatly reduce the cost of raw materials. At the same time, the doping of manganese and / or iron elements can also play a role in fluxing and promote the growth of primary particles, which also helps to increase the powder compaction density of the material; the doping of aluminum elements can also reduce the impedance between the electrolyte and the positive electrode material and improve the battery cycle performance; the doping of titanium elements can also inhibit phase transformation and stabilize the crystal structure, because Ti 4+ The ionic radius is smaller than V 3+ The ionic radius of TiO 6 Octahedron relative to VO 6 The octahedron is more stable.

[0047] In an optional embodiment, the sodium vanadium phosphate composite positive electrode active material is a spherical particle with a particle size Dv50 of 6μm-10μm. Within this particle size range, the spherical particles can be densely packed, thereby ensuring a high powder compaction density of the material. As an example, the particle size Dv50 of the sodium vanadium phosphate composite positive electrode active material can be 6μm, 7μm, 8μm, 9μm, 10μm, etc. or within the range of any two of the above values.

[0048] According to the second aspect of the present application, a method for preparing a sodium vanadium phosphate composite positive electrode active material is provided, comprising the following steps:

[0049] S1. preparing raw materials: a vanadium source, a phosphorus source, a sodium source and a carbon source; mixing the vanadium source with a dispersant, or mixing the vanadium source with a dispersant and any one or two of a phosphorus source, a sodium source and a carbon source to form a first mixture, heating the first mixture to a first temperature and stirring for a first time;

[0050] Then, the remaining raw materials are added, and stirred at the first temperature for a second time to obtain a second mixture with a solid content of 30%-60%; the ratio of the first temperature to the boiling point of the dispersant is 0.6-0.9;

[0051] S2, sand-milling the second mixture obtained in S1 to obtain a third mixture;

[0052] S3, spray drying the third mixture obtained in S2 to obtain spherical particles;

[0053] S4. Heat-treating the spherical particles obtained in S3 in a protective atmosphere to obtain.

[0054] It should be noted that in order to ensure that the insoluble solid raw materials can be evenly dispersed in the liquid, the existing sodium vanadium phosphate preparation process usually requires the use of a surfactant to form a stable suspension or colloid. If the surfactant is added first and then the raw materials, the solvent solubility will be reduced, the raw materials cannot be completely dissolved, the mixing will be uneven, and the slurry reaction will be incomplete; if the raw materials are added first and then the surfactant, the surfactant cannot be completely dissolved, and it is difficult to achieve the purpose of improving the uniformity of the slurry. In addition, the particles of the surfactant itself are relatively large, and if they cannot be completely dissolved, the subsequent sand grinding process cannot be carried out. If the surfactant and the raw materials are to be dissolved at the same time, the solid content of the slurry will be less than 30%, which will slow down the reaction rate between the raw materials, and the final product cannot be balled, and the compaction density is too low.

[0055] In order to solve the above problems, the present application optimizes the order of adding each raw material, and adopts the method of heating and stirring to achieve uniform mixing of the raw materials, sufficient reaction and exhaust, omits the use of surfactants, and increases the solid content of the slurry. As an example, the solid content of the second mixture in the present application can be 30%, 40%, 50%, 60%, etc. or within the range of any two of the above values. This not only shortens the reaction time, but also helps to increase the compaction density of the material. In addition, the preparation method of the present application is simple in process, does not require major changes to the mainstream preparation process, has a short cycle, and is suitable for industrial production.

[0056] Specifically, compared with other raw materials, the solubility of the vanadium source is worse, so the present application first mixes the vanadium source with a dispersant to form a first mixture, and one or two of other raw materials (such as a phosphorus source, a sodium source, and a carbon source) may be added to the first mixture at the same time, or no other raw materials may be added. By heating the first mixture to a first temperature and stirring, the solubility of the vanadium source may be improved. In some embodiments, the vanadium source and the carbon source may be first added to the dispersant and heated and stirred, and while the vanadium source and the carbon source are uniformly dispersed, the redox reaction between the high-valent vanadium and the carbon is slowly started, and then the phosphorus source, the sodium source, and the M source (M source may not be added as appropriate) are added, which can provide an acidic environment for the reaction, accelerate the reduction of vanadium, and ensure that the reaction is completely carried out. Moreover, oxygen, carbon dioxide and other gases are produced as by-products during the reaction process. In the pulping stage, the raw materials are fully contacted and reacted, and a large amount of gas is discharged in time, so that relatively dense particles can be obtained before the heat treatment step. The heat treatment step is mainly a carbonization process, and less gas is produced. On the one hand, the carbon can be coated more tightly, the utilization rate of carbon is improved, and the production cost is reduced. On the other hand, the unevenness of the spheres formed can be avoided, and the high pressure density of the material can be guaranteed on the third hand. In addition, the particles made after all the raw materials are dissolved are hollow spheres, and the compaction density is not high. However, the present application makes the raw materials into a suspension, thereby forming solid particles, which helps to improve the compaction density of the material.

[0057] The present application has found that the ratio of the first temperature to the boiling point of the dispersant is 0.6-0.9. If the first temperature is too high, the dispersant will be evaporated and the solid-solid reaction will be uneven. If the first temperature is too low, the reaction rate will be too slow. It should be noted that the dispersant in the present application includes at least one of deionized water, anhydrous ethanol, anhydrous ether, and anhydrous methanol. If deionized water is used as the dispersant, the first temperature can be, for example, 60°C, 70°C, 80°C, 90°C, etc. or within the range of any two of the above values. If anhydrous ethanol, anhydrous ether, or anhydrous methanol is used as a dispersant, since the above three solvents are flammable, the requirements for production equipment are relatively high, and closed sand mills, closed spray dryers, etc. need to be used.

[0058] In an optional embodiment, the first time is 30 min-90 min, which can ensure that the vanadium source can be evenly dispersed. The second time is 30 min-60 min, which can ensure that the raw materials are evenly mixed and reacted, and the by-product gas is discharged in time. It is understandable that within the second time range of continued stirring, the first temperature can be maintained for reaction, or the reaction can be carried out at room temperature without heating, depending on the reaction situation.

[0059] Since the sodium source will volatilize a little during the heat treatment step, it is necessary to ensure that the molar number of the sodium source is slightly greater than its stoichiometric ratio. In some embodiments of the present application, the molar ratio of the sodium element in the sodium source to the vanadium element in the vanadium source and the phosphorus element in the phosphorus source is (3-3.1):2:3. The ratio of the mass of the carbon source to the total mass of the vanadium source, the phosphorus source and the sodium source is (0.02-0.2):1, thereby obtaining a sodium vanadium phosphate positive electrode material with reasonable ratio, high phase purity and high compaction density.

[0060] In an optional embodiment, the vanadium source includes at least one of vanadium trioxide, vanadium dioxide, vanadium pentoxide, vanadium acetylacetonate, vanadium dichloride, vanadium trichloride, vanadium sulfate, vanadium oxalate, vanadium acetylacetonate, sodium vanadate, sodium metavanadate, and ammonium metavanadate, and the preferred vanadium source is vanadium pentoxide. This is because compared with other vanadium sources, the vanadium element in vanadium pentoxide accounts for a high proportion, produces less gas, and does not contain impurity elements such as chlorine and nitrogen, which will not affect product performance. The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate, and the preferred phosphorus source is sodium dihydrogen phosphate. The sodium source includes at least one of trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium oxide, and sodium peroxide, and it is further preferred that the sodium source is sodium carbonate. The carbon source includes at least one of activated carbon, Ketjen black, carbon nanotubes, graphene, sucrose, cellulose, polyvinyl pyrrolidone, oleic acid, dopamine hydrochloride, oxalic acid, glucose, ascorbic acid, and citric acid. Preferably, the carbon source is glucose.

[0061] Sand grinding is performed before spray drying to control the particle size within a suitable range. In some embodiments, the particle size Dv50 of the third mixture obtained after sand grinding is 0.3μm-1μm. As an example, it can be 0.3μm, 0.5μm, 0.7μm, 0.9μm, 1μm, etc. or within the range of any two of the above values. If the particle size is too large or too small, the compaction density of the material may be low. In order to facilitate spray suction, in some embodiments, it is necessary to further adjust the solid content of the third mixture to within the range of 30%-50%. If the solid content is too high, the spray peristaltic pump cannot pump the slurry to the spray head, and the entire spraying cannot be carried out.

[0062] In some embodiments, the process parameters of the spray drying step include: a pressure of 0.3MPa-0.6MPa, an inlet air temperature of 200℃-260℃, and an outlet air temperature of 100℃-130℃. The present application has found that the inlet air temperature of spray drying has a great influence on the compaction density of the material. Within a certain temperature range, the higher the inlet air temperature, the greater the compaction density. As an example, the inlet air temperature of spray drying can be 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, etc. or within the range of any two of the above values. If the inlet air temperature is too high, the energy consumption of the equipment becomes large, and the adhesion between the powder particles is more serious, which affects the carbon coating effect. On the contrary, if the inlet air temperature is too low, the powder moisture cannot be completely dried, causing the material to stick to the wall, the material loss rate increases, and the unevaporated moisture will be discharged in the sintering section, so that holes appear on the surface of the particles and they break, which ultimately leads to a decrease in the compaction density of the powder. In addition, the pressure of spray drying will also affect the compaction density of the material. Within a certain pressure range, the greater the pressure, the higher the compaction density. However, excessive pressure not only increases energy consumption and equipment loss, but also leads to uneven particle size distribution, affecting product quality and appearance.

[0063] In some embodiments, the heating rate of the heat treatment step is 1°C / min-5°C / min, the calcination temperature is 600°C-850°C, and the calcination time is 6h-20h. This ensures that a pure phase and high compaction density sodium vanadium phosphate material is obtained. The present application found that if the heating rate is too fast, the raw materials cannot fully react, resulting in the appearance of impure phases in the material. On the contrary, if the heating rate is too slow, time and energy consumption will be wasted. If the calcination temperature is too high or the time is too short, the phase will be impure, the carbon source will volatilize seriously, and the carbon coating will be insufficient in the end, and the electrical properties will decrease. On the contrary, the raw materials will not react and sodium vanadium phosphate will not be obtained.

[0064] In some embodiments, S1 further includes the step of adding an M source to the first mixture before forming the first mixture or after heating, wherein the ratio of the sum of the moles of the M element in the M source and the vanadium element in the vanadium source to the moles of the phosphorus element in the phosphorus source is 2:3. The M source includes at least one of a Mn source, a Ti source, a Fe source, and an Al source. The present application does not limit the specific material types of the Mn source, the Ti source, the Fe source, and the Al source, and any existing Mn compound, Ti compound, Fe compound, or Al compound can be applied to the present application.

[0065] According to the third aspect of the present application, a positive electrode plate is also provided, comprising a positive electrode collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode collector, wherein the positive electrode active material layer comprises the sodium vanadium phosphate composite positive electrode active material described in the first aspect of the present application or the sodium vanadium phosphate composite positive electrode active material prepared by the preparation method described in the second aspect of the present application.

[0066] According to the fourth aspect of the present application, a sodium ion battery is also provided, comprising the positive electrode sheet described in the third aspect of the present application. Due to the use of positive electrode active materials with higher compaction density, the sodium ion battery of the present application has the advantages of high energy density, large discharge capacity, small battery internal resistance, high voltage platform, good rate performance and cycle performance.

[0067] The present application is further described in detail below in conjunction with specific examples, and these examples should not be construed as limiting the scope of protection claimed in the present application. Where specific experimental steps or conditions are not specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. Where the manufacturer of the reagents or instruments used is not specified, they are all conventional reagent products that can be obtained commercially.

[0068] Example 1

[0069] This embodiment provides a method for preparing a sodium vanadium phosphate composite positive electrode active material, comprising the following steps:

[0070] S1, V 2 O 5 and 400g of glucose were added to deionized water to form a first mixture, heated to 70°C and stirred for 30min, and then diammonium phosphate and sodium carbonate were added, kept at 70°C and stirred for 60min to obtain a second mixture with a solid content of 40%; wherein the sodium element in the sodium carbonate and V 2 O 5 The molar ratio of the vanadium element in the vanadium and the phosphorus element in the diammonium phosphate is 3.1:2:3.

[0071] S2, passing the cooled second mixture into a sand mill for wet sand grinding, using zirconium beads with a particle size of 0.3 μm-0.5 μm, a sand mill speed of 2400 rpm, and a sand grinding time of 2 h to obtain a third mixture with a particle size Dv50 of 0.3 μm, and adjusting the solid content of the third mixture to 40%;

[0072] S3, sending the third mixture into a spray drying device, controlling the pressure to 0.4 MPa, the air inlet temperature to 240° C., and the air outlet temperature to 110° C., to obtain spherical particles;

[0073] S4. The spherical particles obtained in S3 are sent to a calcination device, and the temperature is increased to 800° C. at a heating rate of 3° C. / min under nitrogen protection, and calcined for 10 hours. The calcined material is cooled and sieved to obtain 500 g of sodium vanadium phosphate composite positive electrode active material.

[0074] Figure 1This is an XRD comparison diagram of the sodium vanadium phosphate composite positive electrode active material prepared in this embodiment and a sodium vanadium phosphate standard card. It can be seen from the figure that Example 1 can synthesize sodium vanadium phosphate with a pure phase.

[0075] Figure 2 : is a SEM picture of the sodium vanadium phosphate composite positive electrode active material prepared in this example. It can be seen that the sodium vanadium phosphate composite positive electrode active material is spherical particles with a particle size Dv50 of 8 μm.

[0076] Figure 3 The cross-sectional SEM image of the sodium vanadium phosphate composite positive electrode active material prepared in this embodiment shows that the sodium vanadium phosphate composite positive electrode active material has a core-shell structure, the core of which is dense sodium vanadium phosphate, and the chemical formula is Na 3 V 2 (PO 4 ) 3 , the surface of the inner core is covered with a carbon layer.

[0077] Figure 4 This is a cycle curve diagram of the sodium vanadium phosphate composite positive electrode active material prepared in this embodiment after assembly and charging. It can be seen that sodium vanadium phosphate has excellent rate performance and excellent cycle retention rate, and can be applied to long-cycle batteries.

[0078] Example 2

[0079] Except for the following contents, the rest is the same as Example 1.

[0080] S1, V 2 O 5 Deionized water was added to form a first mixture, which was heated to 70°C and stirred for 30 minutes, and then diammonium dihydrogen phosphate, sodium carbonate and glucose were added.

[0081] Example 3

[0082] Except for the following contents, the rest is the same as Example 1.

[0083] S1, V 2 O 5 Glucose and ammonium dihydrogen phosphate were added into deionized water to form a first mixture, which was heated to 70° C. and stirred for 30 min, and then sodium carbonate was added.

[0084] Example 4

[0085] Except for the following contents, the rest is the same as Example 1.

[0086] S1, V 2 O 5 Glucose and sodium carbonate were added into deionized water to form a first mixture, which was heated to 70° C. and stirred for 30 min, and then diammonium phosphate was added.

[0087] Example 5

[0088] Except for the following contents, the rest is the same as Example 1.

[0089] The inlet air temperature in S3 is 190℃.

[0090] Example 6

[0091] Except for the following contents, the rest is the same as Example 1.

[0092] The air inlet temperature in S3 is 200°C.

[0093] Example 7

[0094] Except for the following contents, the rest is the same as Example 1.

[0095] The air inlet temperature in S3 is 250°C.

[0096] Example 8

[0097] Except for the following contents, the rest is the same as Example 1.

[0098] The calcination temperature in S4 is 900°C.

[0099] Example 9

[0100] Except for the following contents, the rest is the same as Example 1.

[0101] The calcination temperature in S4 is 700°C.

[0102] Example 10

[0103] Except for the following contents, the rest is the same as Example 1.

[0104] The particle size Dv50 of the third mixture in S2 is 1 μm.

[0105] Embodiment 11

[0106] Except for the following contents, the rest is the same as Example 1.

[0107] The particle size Dv50 of the third mixture in S2 was 1.2 μm.

[0108] Example 12

[0109] Except for the following contents, the rest is the same as Example 1.

[0110] The particle size Dv50 of the third mixture in S2 was 0.2 μm.

[0111] Embodiment 13

[0112] S1, V2 O 5 and 200g of activated carbon were added to deionized water to form a first mixture, heated to 60°C and stirred for 30min, and then phosphoric acid and sodium acetate were added, kept at 60°C and stirred for 60min to obtain a second mixture with a solid content of 50%; wherein the sodium element in the sodium acetate reacts with the V 2 O 5 The molar ratio of vanadium element in phosphoric acid to phosphorus element in phosphoric acid is 3:2:3.

[0113] S2, passing the cooled second mixture into a sand mill for wet sand grinding to obtain a third mixture with a particle size Dv50 of 0.5 μm, and adjusting the solid content of the third mixture to 45%;

[0114] S3, sending the third mixture into a spray drying device, controlling the pressure to 0.6 MPa, the air inlet temperature to 230° C., and the air outlet temperature to 100° C., and performing morphology and particle size control in the spray drying device to obtain spherical particles;

[0115] S4. The spherical particles obtained in S3 are sent to a calcination device, and the temperature is increased to 750° C. at a heating rate of 1° C. / min under nitrogen protection and calcined for 6 hours. The calcined material is cooled and sieved to obtain 500 g of sodium vanadium phosphate composite positive electrode active material.

[0116] Embodiment 14

[0117] S1. Add 100 g of vanadium oxalate and carbon nanotubes into deionized water to form a first mixture, heat to 80° C. and stir for 30 min, then add sodium pyrophosphate, sodium oxalate and manganese carbonate, keep the mixture at 80° C. and continue stirring for 60 min to obtain a second mixture with a solid content of 60%; wherein the molar ratio of the sodium element in sodium oxalate to the vanadium element in vanadium oxalate, the manganese element in manganese carbonate, and the phosphorus element in sodium pyrophosphate is 3.05:1.5:0.5:3.

[0118] S2, passing the cooled second mixture into a sand mill for wet sand grinding to obtain a third mixture with a particle size Dv50 of 0.4 μm, and adjusting the solid content of the third mixture to 50%;

[0119] S3, sending the third mixture into a spray drying device, controlling the pressure to 0.3 MPa, the air inlet temperature to 210° C., and the air outlet temperature to 130° C., and performing morphology and particle size control in the spray drying device to obtain spherical particles;

[0120] S4. The spherical particles obtained in S3 are sent to a calcination device, and the temperature is increased to 850° C. at a heating rate of 5° C. / min under nitrogen protection and calcined for 20 hours. The calcined material is cooled and sieved to obtain 500 g of sodium vanadium phosphate composite positive electrode active material.

[0121] Embodiment 15

[0122] S1. Add vanadium acetylacetonate and 2000 g of citric acid into deionized water to form a first mixture, heat to 90° C. and stir for 30 min, then add diammonium hydrogen phosphate, sodium oxide and aluminum oxide, keep the mixture at 90° C. and continue stirring for 60 min to obtain a second mixture with a solid content of 30%; wherein the molar ratio of the sodium element in the sodium oxide to the vanadium element in the vanadium acetylacetonate, the aluminum element in the aluminum oxide, and the phosphorus element in the diammonium hydrogen phosphate is 3:1.5:0.5:3.

[0123] S2, passing the cooled second mixture into a sand mill for wet sand grinding to obtain a third mixture with a particle size Dv50 of 0.5 μm, and adjusting the solid content of the third mixture to 30%;

[0124] S3, sending the third mixture into a spray drying device, controlling the pressure to 0.5 MPa, the air inlet temperature to 240° C., and the air outlet temperature to 120° C., and performing morphology and particle size control in the spray drying device to obtain spherical particles;

[0125] S4. The spherical particles obtained in S3 are sent to a calcination device, and the temperature is increased to 650° C. at a heating rate of 2° C. / min under nitrogen protection and calcined for 15 hours. The calcined material is cooled and sieved to obtain 500 g of sodium vanadium phosphate composite positive electrode active material.

[0126] Comparative Example 1

[0127] Except for the following contents, the rest is the same as Example 1.

[0128] In S1, all the raw materials are mixed and heated, that is, V 2 O 5 , diammonium dihydrogen phosphate, sodium carbonate and glucose were added to deionized water, heated to 70°C and stirred for 90 minutes, followed by wet sand milling.

[0129] Figure 5 This is a cross-sectional SEM image of the sodium vanadium phosphate composite positive electrode active material prepared in Example 1. It can be seen from the figure that the structure of the secondary particles is relatively loose, resulting in a decrease in the compaction density of the material powder. This is because after all the raw materials are directly mixed, the reaction will occur during the spraying and sintering process, resulting in intense gas production during the spraying and sintering process, causing the primary particles to be unable to combine tightly, thereby forming loose secondary particles.

[0130] Comparative Example 2

[0131] Except for the following contents, the rest is the same as Example 1.

[0132] S1 is not heated, that is, V 2 O5 and glucose were added to deionized water to form a first mixture, which was stirred at room temperature (25° C.) for 30 min, and then ammonium dihydrogen phosphate and sodium carbonate were added, and stirring was continued at room temperature for 60 min.

[0133] Comparative Example 3

[0134] Except for the following contents, the rest is the same as Example 1.

[0135] In S1, after adding diammonium dihydrogen phosphate and sodium carbonate, stirring is performed without heating to obtain a second mixture.

[0136] Comparative Example 4

[0137] Except for the following contents, the rest is the same as Example 1.

[0138] In S1, the first mixture is heated to 50°C.

[0139] Comparative Example 5

[0140] Except for the following contents, the rest is the same as Example 1.

[0141] The solid content of the second mixture obtained in S1 is 20%.

[0142] Test Case

[0143] 1. Powder resistivity test

[0144] Use Yuanneng Technology PDCD1000 powder resistance meter. First, weigh the powder required for the test with weighing paper, and carefully pour the powder into the fixture cavity. The volume of the powder should be kept between 1 / 2 and 2 / 3 of the cavity. Then put the fixture into the pre-vibration instrument to vibrate the powder, take out the fixture, slowly cover the upper gasket, and gently compact the upper gasket with your fingers. Finally, put the powder fixture into the test bench, the protruding part of the test bench needs to be buckled into the fixture groove, and placed steadily, and start the test. Test conditions: pressure 70MPa, pressure holding time 10 seconds.

[0145] 2. Compaction density test

[0146] The compaction density of powders shall be determined in accordance with the provisions of GB / T 24533-2009.

[0147] 3. Carbon content test

[0148] The determination of carbon content shall be carried out in accordance with the provisions of GB / T-20123.

[0149] 4. Particle size test

[0150] The particle size distribution is determined in accordance with the provisions of GB / T 19077.1.

[0151] 5. Electrical performance test

[0152] First, assemble button cells: weigh 1000 mg of the active material prepared in the embodiment or comparative example, 32 mg of the conductive agent Super P and 32 mg of the binder PVDF, grind them thoroughly, add an appropriate amount of NMP to make a slurry, apply them on aluminum foil, dry them, and cut them into round pole pieces for use. In an argon glove box, assemble a CR2016 button cell in the order of negative electrode shell-sodium sheet-electrolyte-diaphragm-electrolyte-positive electrode-positive electrode shell, where the diaphragm is glass fiber and the electrolyte is 1.0M NaClO4 in PC with 5% FEC. Use constant current and constant voltage charge and discharge mode with a voltage range of 2.5 to 4.0V to collect the electrochemical data of the battery.

[0153] The determination of the first discharge specific capacity, first charge and discharge coulombic efficiency, rate performance and cycle retention rate of the powder material withholding test shall be carried out in accordance with the provisions of GB / T 30835.

[0154] The above test results are shown in Table 1.

[0155] Table 1

[0156]

[0157]

[0158] As can be seen from Table 1, compared with Example 1, Comparative Example 1 is to mix all raw materials and heat them, Comparative Example 2 is to first mix the vanadium source and the carbon source but react without heating, Comparative Example 3 is to react the mixture of the vanadium source and the carbon source under heating but only stir without heating after adding diammonium phosphate and sodium carbonate, the heating temperature of Comparative Example 4 is too low, and the solid content of the second mixture formed by the reaction in Comparative Example 5 is low, and the compaction density of the materials obtained is relatively small. This shows that in the preparation process of sodium vanadium phosphate composite materials, the order of adding raw materials and whether to heat are important factors affecting the reaction of raw materials, and the degree of reaction determines the compaction density of the powder.

[0159] The sodium vanadium phosphate composite materials obtained in Examples 1-15 all have a relatively high compaction density, which can reach 1.8 g / cm 3 As mentioned above, the high compaction density of the positive electrode active material represents the high volume energy density of the battery, but other electrical properties such as capacity and cycle should also be taken into account. Therefore, we cannot blindly pursue high compaction density. Taking Example 8 as an example, a higher calcination temperature can improve the compaction density of the material, but too high a calcination temperature will lead to impure material phases, thereby affecting the capacity and cycle stability of the battery.

[0160] The type of carbon source material used to form the carbon coating layer and the coating uniformity determine the powder resistivity of the material. The more uniform the coating, the lower the resistivity. The carbon coating layer formed by glucose can effectively reduce the powder resistivity of the material.

[0161] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A sodium vanadium phosphate composite positive electrode active material, comprising a sodium vanadium phosphate core and a carbon coating layer covering at least a portion of the surface of the sodium vanadium phosphate core; characterized in that: The compaction density of the sodium vanadium phosphate composite positive electrode active material is greater than 1.8 g / cm 3 .

2. The sodium vanadium phosphate composite positive electrode active material according to claim 1, characterized in that: The compaction density of the sodium vanadium phosphate composite positive electrode active material is 1.82 g / cm 3 -2.45g / cm 3 ; And / or, based on the mass of the sodium vanadium phosphate composite positive electrode active material, the content of the carbon coating layer is 1%-6%.

3. The sodium vanadium phosphate composite positive electrode active material according to claim 1 or 2, characterized in that: The general chemical formula of the sodium vanadium phosphate core is Na 3+y V 2-x M x (PO4)3, wherein M is at least one of Mn, Ti, Fe, and Al, 0≤x≤1, 0≤y≤0.5; And / or, the sodium vanadium phosphate composite positive electrode active material is a spherical particle with a particle size Dv50 of 6 μm-10 μm.

4. A method for preparing a sodium vanadium phosphate composite positive electrode active material, characterized in that: The steps include: S1. preparing raw materials: a vanadium source, a phosphorus source, a sodium source and a carbon source; mixing the vanadium source with a dispersant, or mixing the vanadium source with a dispersant and any one or two of a phosphorus source, a sodium source and a carbon source to form a first mixture, heating the first mixture to a first temperature and stirring for a first time; Then, the remaining raw materials are added, and stirred at the first temperature for a second time to obtain a second mixture with a solid content of 30%-60%; the ratio of the first temperature to the boiling point of the dispersant is 0.6-0.9; S2, sand-milling the second mixture obtained in S1 to obtain a third mixture; S3, spray drying the third mixture obtained in S2 to obtain spherical particles; S4. Heat-treating the spherical particles obtained in S3 in a protective atmosphere to obtain.

5. The method for preparing the sodium vanadium phosphate composite positive electrode active material according to claim 4, characterized in that: The first time is 30min-90min; And / or, the second time is 30min-60min; And / or, the molar ratio of the sodium element in the sodium source to the vanadium element in the vanadium source and the phosphorus element in the phosphorus source is (3-3.1):2:3; And / or, the ratio of the mass of the carbon source to the total mass of the vanadium source, the phosphorus source and the sodium source is (0.02-0.2):1; And / or, the dispersant includes at least one of deionized water, anhydrous ethanol, anhydrous ether, and anhydrous methanol.

6. The method for preparing the sodium vanadium phosphate composite positive electrode active material according to claim 5, characterized in that: The vanadium source includes at least one of vanadium trioxide, vanadium dioxide, vanadium pentoxide, vanadium acetylacetonate, vanadium oxychloride, vanadium oxytrichloride, vanadium oxysulfate, vanadium oxyoxalate, vanadium oxyacetylacetonate, sodium vanadate, sodium metavanadate, and ammonium metavanadate; And / or, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, trisodium phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate; And / or, the sodium source includes at least one of trisodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium pyrophosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium oxide, and sodium peroxide; And / or, the carbon source includes at least one of activated carbon, Ketjen black, carbon nanotubes, graphene, sucrose, cellulose, polyvinyl pyrrolidone, oleic acid, dopamine hydrochloride, oxalic acid, glucose, ascorbic acid, and citric acid.

7. The method for preparing the sodium vanadium phosphate composite positive electrode active material according to claim 4, characterized in that: The particle size Dv50 of the third mixture is 0.3 μm-1 μm; And / or, the process parameters of the spray drying step include: pressure of 0.3MPa-0.6MPa, air inlet temperature of 200°C-260°C, and air outlet temperature of 100°C-130°C; And / or, the heating rate of the heat treatment step is 1°C / min-5°C / min, the calcination temperature is 600°C-850°C, and the calcination time is 6h-20h.

8. The method for preparing the sodium vanadium phosphate composite positive electrode active material according to any one of claims 4 to 7, characterized in that: S1 also includes the step of adding an M source to the first mixture before forming the first mixture or after the first mixture is heated; The M source includes at least one of a Mn source, a Ti source, a Fe source, and an Al source, and / or the ratio of the sum of the molar numbers of the M element in the M source and the vanadium element in the vanadium source to the molar number of the phosphorus element in the phosphorus source is 2:

3.

9. A positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, characterized in that: The positive electrode active material layer comprises the sodium vanadium phosphate composite positive electrode active material according to any one of claims 1 to 3 or the sodium vanadium phosphate composite positive electrode active material prepared by the preparation method according to any one of claims 4 to 8.

10. A sodium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Coated modified sodium vanadium phosphate composite positive electrode material as well as preparation method and application thereof

    CN121687910A